STRATEGI PENGEMBANGAN WISATA D’MOOAT DI DESA MOAT KECAMATAN MOOAT KABUPATEN BOLAANG MONGONDOW TIMUR - Amelia Priska Hontong; Tommy Fredy Lolowang; Agnes Estephina Loho (AGRI-SOSIOEKONOMI, 2020)
The purpose of this study was to determine the D'MOOAT Tourism development strategy in Moat Village, Moat District, Bolaang Mongondow Regency. This research lasted for 3 months, from February to April 2019. The data used in this study were primary data and secondary data. Primary data were obtained from direct interviews with 51 people consisting of D’MOOAT owners, employees, Sangadi (Head of Village) and visitors who came to the tourist attractions. This study uses a SWOT analysis model (Strengths, Weaknesses, Opportunity, Threats). The results showed that the D'MOOAT tourist attraction has a very attractive tourist attraction that offers a natural panorama of the moat lake where the playground for children also offers a view of the strawberry garden and ornamental flowers which are an attraction for tourists who come to these attractions.*eprm*